[Géza M. Kovács 2]
in the garden of a weekend house, sunset "golden bridge", children playing, little child kissing grandma', Christmas, family, presents, birthday cake with 5 candles, the Danube, Dömös, Esztergom, Visegrád, a competition of a pioneer-group, summer, bees, flowers, Christmas, sparkler, modern church, mass, scool-ceremony, birthday cake 6 candles, many children, Christmas present